Analisa Strategi Promosi Dinas Pariwisata dan Kebudayaan dalam Meningkatkan Jumlah Kunjungan Wisatawan di Kabupaten Kerinci - Edia Satria (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This research was conducted to find out and prove empirically promotion strategies of cultural tourism and in increasing the number of tourists visit Kerinci Regency. Source data obtained from the Department of tourism and culture District Kerinci. Data analysis tools by using SWOT analysis. The research results obtained that (1) the cultural and Tourism Office of District 1 quadrant is at Kerinci (positive, positive) which means the primacy of kompotitif or aggressive strategies of Cultural tourism and the Regency of Kerinci has the power as well as opportunities to continue to improve and enlarge the number of promotional visits to the Regency of Kerinci; and (2) the right marketing strategies applied to Kerinci District Tourism Office for the moment is a strategy SO (strength, Opportunities). This strategy is underway to harness the power for the menagkap opportunities that are owned. As for the strategies that can be applied include (a) the Kerinci Regency Tourism Office must keep working to develop tourism in Kerinci Regency; (b) Tourism District's tourism should control Keerinci well; (c) the coordination of Tourism with Government Kabuapeten Kerinci must continue to be improved; (d) the Services provided should be constantly improved; and (e) to add visits to the County of Kerinci, tourism and Culture must make use of technology and facilities available, doing promotions, and socialization as many to the community to reach. Keywords: Promotion Strategy